The Mechanism of International Economic Sanctions Influence on the National Economy (Example of Russian Federation) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In the article the concept of international economic sanctions is explained; the historical practice of international economic sanctions and effective enforcement criteria are considered; areas, stages, and effects of international economic sanctions against the Russian Federation are defined; prospects of a national economy in the sanctions regime are investigated.
Keywords: international economic sanctions, Russian Federation, international economic relations